Electric Field Writing of Ferroelectric Nano‐Domains Near 71° Domain Walls with Switchable Interfacial Conductivity. Issue 8 (15th July 2018) - Yang, Shuzhen; Peng, Ren‐Ci; He, Qing; Huang, Yen‐Lin; Huang, Yijing; Yang, Jan‐Chi; Chen, Tianzhe; Guo, Jingwen; Chen, Long‐Qing; Chu, Ying‐Hao; Nan, Ce‐Wen; Yu, Pu
Abstract: Conducting ferroelectric domain walls attract a wide range of research interest due to their promising applications in nanoelectronics. In this study, we reveal an unexpected enhanced conductivity near the well‐aligned 71° nonpolar domain walls in BiFeO3 . Such an interfacial conductivity is induced by the creation of up‐polarized nano‐domains near the 71° domain walls, as revealed by the combination of the piezo‐response force microscopy (PFM) and conducting atomic force microscopy (c‐AFM) imaging techniques, as well as phase‐field simulations. The upward polarized domains are suggested to lower the Schottky barrier at the interface between the tip and sample surface, and then give rise to the enhanced interfacial conductivity. The result provides a new strategy to tune the local conductance in ferroelectric materials and opens up new opportunities to design novel nanoelectronic devices. Abstract : A series of distinct conducting regions are observed near the 71° domain walls in ferroelectric BiFeO3 thin film, which can be attributed to the emergence of metastable nanodomains with the switching of ferroelectric polarization from downward to upward. More specifically, the Schottky barrier height across the conducting atomic force microscope (c‐AFM) tip and sample surface is dramatically reduced with the upward ferroelectric state, and as a consequence, the interfacial conductivity is enhanced.